Trends and Patterns in Primary Education Research: A Bibliometric Review of Instructional and Teacher Education Studies - Adeoye, Moses Adeleke (Profesi Pendidikan Dasar, 2025)
In recent years, primary education has gained increased scholarly and policy attention due to its critical role in shaping foundational learning and long-term academic outcomes. This study addresses this gap by conducting a bibliometric analysis of 85 peer-reviewed publications from 2015 to 2025, focusing on trends and patterns in instructional and teacher education research within primary education. The primary objectives were to map publication output, identify key contributors and institutions, examine collaborative networks, and reveal emerging themes. Relevant data were retrieved from the Scopus database and subjected to bibliometric analysis through a combination of performance analysis and science mapping to visualise co-authorship patterns, keyword co-occurrences, and citation networks. Findings revealed a significant increase in research output over the decade, particularly after 2017, with notable contributions from both high-income and emerging economies. Thematic analysis uncovered four dominant clusters: instructional strategies, teacher preparation, curriculum reform, and inclusive education, with growing attention to digital pedagogy and equity since 2020. This study concludes that while the field has matured in scale and scope, international collaboration remains limited, and certain critical areas—such as gender-sensitive pedagogy and rural instruction—remain underexplored